Effect of NPK Fertilizer and Foliar Fertilizer on Chili Growth and Yield - Anatalia, Rahma; Harsono, Puji; Yunindanova, Mercy Bientri; Purnomo, Djoko (Agrotechnology Research Journal, 2022)
Chili consumption in Indonesia has increased. Efforts to increase chili production need fertilization through roots and leaf fertilization. The research aimed to obtain optimum intervals of NPK (nitrogen, phosphor, potassium) fertilization and kinds of foliar fertilizer for the growth and yield of chili. The research was conducted from April to August 2020 in Gayam Village, Sukoharjo Regency, Central Java, Indonesia. This study used an experiential method with a Randomized Complete Block Design (RCBD) of 2 factors. The first factor was an interval of NPK fertilization (16-16-16) with a concentration of 25 g.L-1 with a dose of 240 mL.plant-1. The interval of NPK fertilization consists of 4 levels, NPK fertilizer which was applied every 5, 10, 15, and 21 days. The second factor was foliar fertilizer which consists of A foliar fertilizer, B foliar fertilizer, and C foliar fertilizer. The results showed that the interval of NPK fertilizer affected the number of dichotomous branches, dry stove weight, cumulative fruit, cumulative fruit weight, and fruit length at 1st harvest. NPK fertilization every 15 days increased the dichotomous branches by 23.16%, dry stove weight by 37.98%, cumulative fruits by 37.41%, and cumulative fruit weight by 41.46%. B foliar fertilizer and A foliar fertilizer gave the same performance in dichotomous branches. There was no interaction effect between the interval of NPK fertilization and the kind of foliar fertilizer on all growth and yield variables. NPK fertilization optimum intervals as supplementary fertilizers should be given every 15 days. This research can be used as a reference for farmers in fertilizing chilies.